Clinical pathology and laboratory techniques for veterinary technicians - Barger, Anne M.; MacNeill, Amy L. (Ames, Iowa : Wiley-Blackwell, 2015)
'Provides information on hematology, hemostasis, clinical chemistry, urinalysis, parasitology, and fecal testing'--Provided by publisher.
Machine generated contents note: Getting Started with Clinical Pathology -- Hematology -- Hemostasis -- Clinical Chemistry -- Urinalysis -- Parasitology -- Minimizing Laboratory Errors in Veterinary Practice.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Veterinary clinical pathology; Clinical Laboratory Techniques -- veterinary; Animal Technicians; Pathology, Clinical -- methods; Pathology, Veterinary -- methods; Electronic books